IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR ENTITIES WITHOUT PUBLIC ACCOUNTABILITY (SAK-ETAP) IN SMALL AND MEDIUM ENTERPRISES (SMEs) (Case Study on Pratama Parfum in Pontianak) - B1034141024, Melvieni Riza Chaniago (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
ABSTRACT Financial Accounting Standards for Entities without Public Accountability (SAK ETAP) are financial accounting standards established to facilitate the preparation and presentation of financial statements for SMEs. The information presented in the financial statements can provide convenience for SMEs when they want to borrow from banks or collaborate with other parties. This study was designed to produce a simple financial report format based on SAK ETAP for SMEs.The object of this study is the SMEs Pratama Parfum located at Jalan Sepakat 2 Ahmad Yani No. 80 Pontianak. This SMEs is engaged in selling goods in the form of perfumes and perfume bottles. The purpose of this study was to determine the implementation of SAK ETAP in Pratama Parfum SMEs and to find out the obstacles that make these SMEs unable to make financial reports that are in accordance with SAK ETAP. Based on the existing problems, the researcher devised a financial report in the form of a Statement of Financial Position, Income Statement, Changes of Owner Equity Statement, Cash Flow Statement, and Notes to Financial Statement.This research is descriptive qualitative research, and data collection used is through observation, interviews, documentation, and literature study. The conclusion of the results of the research that has been done is that the financial statements of the Pratama Parfum SMEs have not implemented SAK ETAP. The factor that caused SMEs to not implement SAK ETAP in their financial statements was due to a lack of accounting understanding of SMEs owners, as well as a lack of participation from the government to conduct socialization and training of SMEs regarding SAK ETAP.                              Keywords: SAK ETAP, Financial Statement, SMEs. REFERENCES  Bahri, S. (2016). Pengantar Akuntansi Berdasarkan SAK ETAP dan IFRS. Yogyakarta: CV. ANDI OFFSET.Eka, I. W. (2010). SAK ETAP, sebuah versi sederhana dari SAK Umum. Retrieved from Daun Lontar: https://iwayanaguseka.com/2010/02/21/sak-etap-sebuah-versi-sederhana-dari-sak-umum/Frilisia, F., & Wirajaya, I. G. (2018). Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Pada PT. Aira Nusantara Indah. E-Jurnal Akuntansi Universitas Udayana, Vol.23.1.Hery. (2016). Analisis Laporan Keuangan-Integrated And Comprehensive Edition. Jakarta: PT. Grasindo.Bank Indonesia. (2015). Retrieved from www.bi.go.id.IAI. (2009). Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik. Jakarta: Divisi Penerbitan IAI.IAI. (2016). Standar Akuntansi Keuangan Efektif Per 1 Januari 2017. Jakarta: Divisi Penerbitan IAI.Jimi. (2017). Analisis Penerapan Standar Akuntansi Keuangan Untuk Entitas Tanpa Akuntabilitas Publik (SAK-ETAP) Pada Usaha Mikro Kecil dan Menengah (UMKM) Toko Bangunan "Sutomo Jaya". Pontianak: Universitas Tanjungpura, undergraduate thesis.Kasmir. (2012). Analisis Laporan Keuangan. Jakarta: PT. Raja Grafindo Persada.Kieso, D. E., Weygandt, J. J., & Warfield, T. D. (2012). Intermediate Accounting. Hoboken, New Jersey: John Wiley & Sons, Inc.Kristanto, E. (2011). Penerapan Standar Akuntansi Keuangan Untuk Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Pada UMKM Pengrajin Rotan di Desa Trangsan Kecamatan Gatak Kabupaten Sukoharjo. Surakarta: Universitas Sebelas Maret, undergraduate thesis.Martani, D. (2012). Akuntansi Keuangan Menengah Berbasis PSAK. Jakarta: Salemba Empat.Merina, N. (2018). Pengertian UKM & UMKM? Bagaimana Usaha Kecil Menengah di Indonesia. Retrieved from GOukm.id.Norkamsiah, Kesuma, A. I., & Setiawaty, A. (2016). Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Pada Penyusunan Laporan Keuangan. Jurnal Ekonomi dan keuangan Volume 13, (2), http://journal.feb.unmul.ac.id.Pratama, A. (2014). Rancangan Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Pada Usaha Kecil dan Menengah (UKM). Jakarta: Universitas Islam Negeri Syarif Hidayatullah, undergraduate thesis.Pratiwi, A. A., Sondakh, J. J., & Kalangi, L. (2014). Analisis Penerapan SAK ETAP Pada Penyajian Laporan Keuangan PT. Nichindo Manado Suisan. Jurnal EMBA Vol.2 No.3, 254-265.Purwanti, A. (2015). Penerapan Standar Akuntansi Keuangan Untuk Entitas Tanpa Akuntabilitas Publik (SAK-ETAP) Pada Usaha Kecil Menengah (UKM) Boutique Save Fashion. Pontianak: Universitas Tanjungpura, undergraduate thesis.Rudiantoro, R., & Siregar, S. V. (2012). Kualitas Laporan Keuangan UMKM Serta Prospek Implementasi SAK ETAP. Jurnal Akuntansi dan Keuangan Indonesia, Volume 9 - No. 1.Sakti, A. L. (2017). Analisis Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Pada Usaha Mikro Kecil dan Menengah (UMKM) (Studi Kasus pada Tria's Cake & Bakery di Blitar). Malang: Universitas Islam Negeri Maulana Malik Ibrahim, undergraduate thesis.Susanti, K. (2015). Analisis Penerapan Akuntansi Pada Usaha Kecil Menengah (Studi Pada Usaha Fotocopy di Kota Pontianak). Pontianak: Universitas Tanjungpura, undergraduate thesis.Tribun Pontianak. (2017, Februari 26). Ada 108 Ribu UMKM di Kalbar, Namun Masih Banyak Yang Tak Percaya Diri. Pontianak, Kalimantan Barat, Indonesia.Tribun Pontianak. (2018, April 18). Kini Pontianak Miliki 17 Ribu Pelaku UMKM, Ini Target Pemkot. Pontianak, Kalimantan Barat, Indonesia.Undang-Undang Republik Indonesia Nomor 20 Tahun 2008 Tentang Usaha Mikro, Kecil, dan Menengah. (n.d.).Wikiapbn. (2015). Karakteristik Kualitatif Laporan Keuangan. Retrieved from www.wikiapbn.org.Yadiati, W., & Mubarok, A. (2017). Kualitas Pelaporan Keuangan. Jakarta: KENCANA.